Prevalence and predictive factors of complementary medicine use during the first wave of the COVID-19 pandemic of 2020 in the Netherlands - Louise T. C. Mulder; Martine Busch; Agnete E. Kristoffersen; Johanna Hök Nordberg; Esther T. van der Werf (BMC, 2022)
Abstract Introduction Major life changing events such as the COVID-19 pandemic may have major impact on one's health and general well-being. This study aimed to determine the prevalence and predictive factors, including gender specific differences, of Complementary Medicine (CM) use (including CM consultations, self-care management and self-help techniques) during the first wave of the COVID-19 pandemic in 2020 in the Netherlands. Methods CM use was studied among a random representative sample (n = 1004) of the adult Dutch population using an online survey conducted from 22-27 May 2020. The survey included a modified version of I-CAM-Q and additional questions on demographic characteristics, reasons for CM use, perceived effectiveness and side effects. Results 68.0% of the participants reported to have used CM (CM consultations (13.3%), self-management strategies (59.4%), self-help techniques (30.0%)). Most frequently reported reason of CM use was to improve general well-being (61.6%), prevention and/or treatment of COVID-19 was only reported by 10%. Perceived effectiveness of CM was high and number of experienced side effects low. Being a women, worried to get infected with COVID-19, higher education and living in northern/ middle region of the Netherlands were predictive factors to use CM. Conclusions In the Netherlands, specific groups (e.g. women/ highly educated) use CM, mainly to improve general wellbeing, and seem to benefit of it during the first months of the pandemic. The high perceived effectiveness and low reporting of side effects should encourage medical professionals and policy makers for more openness towards considering CM as being part of an integrative approach to public health in times life changing events occur.